The Effect of Investment Policy, Funding Policy, and Asset Management on Firm Value - Syntia Cipta Ningrum; Sawitri Dwi Prastiti; Yohanes Sri Guntur (Universitas Negeri Malang, 2024)
Purpose: This study aims to explain the effect of investment policy, funding policy, and asset management on firm value. The theory used to explain the relationship between variables in the research model is agency theory.Method: Data was collected from 65 samples of mining sector companies listed on the Indonesia Stock Exchange between 2015 and 2019. Using panel data, this study used panel regression analysis to explain the relationship between variables.Findings: The test results indicate that investment policy and funding policy do not affect firm value. Asset management has a significant positive effect. The effect of asset management on firm value also confirms agency theory.Originality/ValueThis study used a research sample of mining sector companies for the 2015-2019 period which faced pressure in the form of falling demand for Indonesian mining commodities in the world market and issues of environmental damage. The financial condition of the mining sector in the research period generally experienced financial difficulties due to these pressures.